Intravenous immunoglobulin for the prevention of infection in chronic lymphocytic leukemia. A randomized, controlled clinical trial. Cooperative Group for the Study of Immunoglobulin in Chronic Lymphocytic Leukemia. - Gamm, H; Gerhards, U; Mertelsmann, R; Dicato, M; Lallemang, J; Maisin, F; Gale, R; Desai, R; Gabor, P; Greenberg, L; Richardson, H; Chapel, H; et al. (1988)
In a double-blind study, we randomly assigned 84 patients with chronic lymphocytic leukemia who were judged to be at increased risk of bacterial infection to receive intravenous immunoglobulin G (400 mg per kilogram of body weight) or a placebo every three weeks for one year. Eligible patients had hypogammaglobulinemia, a history of infection, or both. The patients receiving immunoglobulin had significantly fewer bacterial infections during the study period than those receiving placebo (23 vs. 42; P = 0.01). This reduction was most striking in the patients who completed a full year of treatment (14 vs. 36; P = 0.001). The period from study entry to the first serious bacterial infection was significantly longer in the patients receiving immunoglobulin (P = 0.026). There was no significant difference between the two groups in the incidence of nonbacterial infection. Immunoglobulin therapy was tolerated well; there were no serious adverse reactions, and the incidence of minor reactions was low. We conclude that selected patients with chronic lymphocytic leukemia who are at risk of bacterial infection can be substantially protected from this complication by the regular intravenous administration of immunoglobulin.